Analysis of Harmonics Influences on Load Switching Transients in Simple Power System - Arikan, Oktay; Kocatepe, Celal; Yumurtaci, Recep (IEEE, 2008)
This paper presents the transient analysis of a simple power system. Measurements are taken from a simple system that takes place at Turkish National Power System. Matlab Simpower Toolbox is used for the analysis. Dynamic analysis of the system studied for switching operations. Effects of load acception and reduction are studied as switching operations. Constant impedance load model is used for the simulations. At the case study, added loads have different harmonic components for analyzing effects of harmonics to the system. Harmonic components of the load current are modeled by using current injection method.
Keywords: Transmission line; harmonics; total harmonic distortion; transient; Energy & Fuels; Engineering